2021
DOI: 10.3390/molecules26154435
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Antioxidant and Anti-Inflammatory Properties of the Biological Extracts of Psophocarpus tetragonolobus Using Two Extraction Methods

Abstract: Psophocarpus tetragonolobus has long been used in traditional medicine and cuisine. In this study, Psophocarpus tetragonolobus extracts were isolated by maceration and ultrasound-assisted extraction and were evaluated for their antioxidant and anti-inflammatory effects in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. The obtained results show that both extracts (maceration and ultrasound) were rich in bioactive molecules and exerted substantial antioxidant and anti-inflammatory effects. The P. tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…It is a member of Fabaceae family and is high in protein, oils, vitamins, and carbohydrates [45]. It has been reported that winged bean seed hydrolysate is non-toxic and can stimulate cell proliferation in NIH/3T3 mouse fibroblast cells [46] and winged bean extract was non-toxic to RAW264.7 macrophage cells [47]. These studies reveal the healthpromoting activity and safety of this legume.…”
Section: Resultsmentioning
confidence: 91%
“…It is a member of Fabaceae family and is high in protein, oils, vitamins, and carbohydrates [45]. It has been reported that winged bean seed hydrolysate is non-toxic and can stimulate cell proliferation in NIH/3T3 mouse fibroblast cells [46] and winged bean extract was non-toxic to RAW264.7 macrophage cells [47]. These studies reveal the healthpromoting activity and safety of this legume.…”
Section: Resultsmentioning
confidence: 91%
“…Subsequently, 1 mL of extract was combined with 1 mL of NaOH (Sigma-Aldrich Co., St. Louis, MO, USA) and heated for 5 min at 100 °C. The presence of anthocyanins was indicated by the appearance of a bluish-green color [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, 1 ml of NaOH was added to 1 ml of the extract and heated for 5 min at 100°C. The presence of a bluish-green color indicated the presence of anthocyanin ( Bassal et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%